Why do Some Elite Players Accomplish their Grand Slam Goals While others Fail? - Djurovic, Niksa; Stanisic, Ljubica; Sbarro, Fabrice (ITF Coaching & Sport Science Review, 2014)
When coaches talk about talent as the most important predictor of success, often we find through practical case studies that this hypothesis could not be confirmed. The question is: What is talent and are we missing something? The intention of the article is to accelerate the player’s development and ultimately maximise their potential while directing coaches to core problems.